2014
DOI: 10.1039/c4ra06978a
|View full text |Cite
|
Sign up to set email alerts
|

Novel thermosensitive telechelic PEGs with antioxidant activity: synthesis, molecular properties and conformational behaviour

Abstract: We report on the synthesis and solution properties of novel tailor -made polymer conjugates, which are highly compelling for biomedical applications due to their antioxidant activity and the potential to fine-tune their thermosensitive properties. These conjugates consist of polyethylene glycol (PEG polymers containing antioxidant moieties, namely 3 -(3,5-di-tertbutyl-4-hydroxyphenyl)propionate or 2-benzamido-3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylate, as end groups that differ in activity and hydrophobicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…The ability to reduce CPT by introducing a hydrophobic moiety has been reported previously for a variety of copolymers. [42][43][44] The incorporation of hydrophilic PEG as a central block creates an opposing trenda CPT value that increases, as was previously observed for PNIPAM-b-PEG-b-PNIPAM copolymer. 27 Calculated intensity weighted distribution functions of the hydrodynamic radius Rh show a bimodal distribution at 25 °C and a monomodal distribution at 40 °C (Figure 2b, inset).…”
Section: Temperature Behaviour Of Pnipam-b-pdms-b-pnipamsupporting
confidence: 62%
“…The ability to reduce CPT by introducing a hydrophobic moiety has been reported previously for a variety of copolymers. [42][43][44] The incorporation of hydrophilic PEG as a central block creates an opposing trenda CPT value that increases, as was previously observed for PNIPAM-b-PEG-b-PNIPAM copolymer. 27 Calculated intensity weighted distribution functions of the hydrodynamic radius Rh show a bimodal distribution at 25 °C and a monomodal distribution at 40 °C (Figure 2b, inset).…”
Section: Temperature Behaviour Of Pnipam-b-pdms-b-pnipamsupporting
confidence: 62%
“…The sample changer is particularly helpful for projects that require the measurement of large numbers of samples under varying conditions. An example can be found in Sergeeva et al (2014), where the authors studied the solution properties of several tailor-made polyethylene glycol polymers with antioxidant moieties at different concentrations and temperatures. The high-throughput and extensive screening possibilities offered by the Sample Changer permitted full automation of the measurements and the rapid extraction of phase diagrams of the polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic comonomers favorable to segment-segment interactions in polymer tend to decrease the LCST, whereas hydrophilic comonomers favorable to segment-solvent interactions have the opposite effect [84,85]. Triblock copolymers MeOX-(iPrOX-co-BuOx)-MeOX with thermoresponsive properties were reported by Hruby et al [40] It was found that as the temperature increases, the polymers transform from single molecules to loose aggregates to compact nanoparticles.…”
Section: Responsivity To Temperaturementioning
confidence: 91%